Spin flipping a stored polarized proton beam with an rf dipole - V. A. Anferov; B. B. Blinov; D. Yu. Kantsyrev; A. D. Krisch; D. W. Sivers; C. M. Chu; P. Schwandt; B. von Przewoski; V. N. Grishin (Physical Review Special Topics. Accelerators and Beams, 2000)
We recently studied the spin flipping of a 202.7 MeV vertically polarized proton beam stored in the Indiana University Cyclotron Facility cooler ring during the first polarized run with its new cooler injector synchrotron and its new cooler injector polarized ion source. We first set the vertical betatron tune to avoid the measured ν_{y} value of the Gγ=7-ν_{y} intrinsic depolarizing resonance in the cooler ring. We then flipped the spin by ramping the frequency of an rf dipole through an rf-induced depolarizing resonance. After optimizing the rf dipole's frequency ramp parameters, we used multiple spin flips to measure a maximum spin-flip efficiency of 97.5±1%.